2020
DOI: 10.1111/1759-7714.13596
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of image‐guided radiotherapy for locally advanced lung cancer patients treated with definitive concurrent chemoradiotherapy

Abstract: Background Image‐guided radiotherapy (IGRT) is an advanced radiotherapy technique to improve the precision and accuracy of treatment delivery. A recent randomized controlled trial (RCT) for prostate cancer patients treated with radiotherapy via either IGRT or routine care reported statistically significantly worse overall survival (OS) for those patients treated with IGRT. This raised the concern regarding the effectiveness of IGRT in definitive concurrent chemoradiotherapy (dCCRT) for locally advanced lung ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To account for potential nonrandomized treatment selection, the following covariates were collected, based on recent relevant studies and our clinical research experiences: [5,[8][9][10]18] patient demographics (age, sex, residency region, and socioeconomic status (SES)), patient characteristics (body mass index (BMI), comorbidity, smoking, and performance status), and disease characteristics (clinical T-and N-stage, tumor size).…”
Section: Covariatesmentioning
confidence: 99%
“…To account for potential nonrandomized treatment selection, the following covariates were collected, based on recent relevant studies and our clinical research experiences: [5,[8][9][10]18] patient demographics (age, sex, residency region, and socioeconomic status (SES)), patient characteristics (body mass index (BMI), comorbidity, smoking, and performance status), and disease characteristics (clinical T-and N-stage, tumor size).…”
Section: Covariatesmentioning
confidence: 99%
“…Published evidence on the role of image-guided radiation therapy (IGRT) in SCLC is limited. One study involving a series of 132 patients with SCLC[ 170 ] found no significant differences in OS between patients treated with or without IGRT. No toxicity information was reported.…”
Section: Rt Techniquesmentioning
confidence: 99%
“…The covariates were modified from the literature 12 as well as our experiences in clinical care 13 and TCR studies. 14,15…”
Section: Study Population and Study Designmentioning
confidence: 99%